2018
DOI: 10.1016/j.visres.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of low vision aids to reading accessibility

Abstract: The Reading Accessibility Index (ACC) has been proposed as a single-value reading parameter that can capture information on both reading speed and print sizes that can be read. It is defined as the average reading speed across a relevant range of print sizes (1.3-0.4logMAR), normalised by typical young-adult reading speed of 200wpm, and with values typically in the range of 0-1. This study determines the impact of low vision aids (LVAs) on reading by evaluating ACC values for visually impaired observers readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
(48 reference statements)
1
8
1
Order By: Relevance
“…A disadvantage of the sample is that the causes of visual loss are not necessarily ‘typical’ of a group of low vision patients and does not include a large number of participants with central field loss (e.g., those with macular degeneration). However, in previous studies considering reading, 16,18,21 we have not found differences between individuals with specifically central visual loss and those with other conditions. The level of visual function has been the important discriminating factor for performance, rather than the cause of visual loss.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…A disadvantage of the sample is that the causes of visual loss are not necessarily ‘typical’ of a group of low vision patients and does not include a large number of participants with central field loss (e.g., those with macular degeneration). However, in previous studies considering reading, 16,18,21 we have not found differences between individuals with specifically central visual loss and those with other conditions. The level of visual function has been the important discriminating factor for performance, rather than the cause of visual loss.…”
Section: Discussioncontrasting
confidence: 70%
“…36,37 A disadvantage of the sample is that the causes of visual loss are not necessarily 'typical' of group of low vision patients and does not include a large number of participants with central field loss (e.g., those with macular degeneration). However, in previous studies considering reading, 16,18,21 we have not found differences between individuals with specifically central visual loss and those with F I G U R E 4 Maximum reading speed (MRS) in words per minute (wpm) derived by inspection compared to the first judgments of reading speed by rater 1 (blue symbols) and rater 2 (orange symbols). The solid horizontal line represents a measured MRS of 80 wpm, and the dashed line a measured MRS of 120 wpm T A B L E 2 Summary of the ability of each rater to judge whether the maximum reading speed (MRS) was 'functional' (>80 wpm) or 'nonfunctional' (<80 wpm) Note: Category options as for Table 3.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
See 1 more Smart Citation
“…9 Low vision rehabilitation can help patients with moderate to severe low vision improve in their clinical reading ability, as well as overall reading speed. 10 The LOVIT-II study 11 demonstrated that basic low vision services (i.e., visual assistive device dispensed at a single in-office training session without ongoing rehabilitation therapy or homework) are effective in patients with mild vision impairment. Although randomized clinical trials are needed to better understand low vision rehabilitation outcomes in patients with mild vision impairment outside of the Veteran's Affairs system, these initial results indicate that basic low vision services can be effectively integrated into a primary care optometric practice.…”
mentioning
confidence: 99%
“…Overall, these magnification tools have been shown to increase reading ability of low-vision patients for standard news print [10,11]. However, there is a strong trade-off between portability (i.e., whether the user is required to sit at a desk) and screen space (i.e., how much content can be seen through the magnifier).…”
Section: Printmentioning
confidence: 99%